The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1161/01.str.0000038989.90931.be
|View full text |Cite
|
Sign up to set email alerts
|

Association of Obesity and Central Fat Distribution With Carotid Artery Wall Thickening in Middle-Aged Women

Abstract: Background and Purpose-The association between obesity and atherosclerotic disease is controversial. In the present analysis, we evaluated whether common carotid intima-media thickness (IMT) and area, 2 markers of preclinical atherosclerosis, were increased in obese subjects. Methods-More than 5000 middle-aged women (nϭ5062; age, 30 to 69 years) living in the area of Naples, Southern Italy, were recruited for a prospective, currently ongoing study on the etiology of cardiovascular disease and cancer in the fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
97
2
7

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(121 citation statements)
references
References 43 publications
15
97
2
7
Order By: Relevance
“…4 A graded and independent association of WHR and BMI with carotid IMT was found in a cross-sectional study in middle-aged women. 12 WHR and BMI were also directly associated with carotid IMT in a crosssectional study among Japanese men aged 20-78 years. 23 Some studies have not shown an independent association of BMI 14 or measures of abdominal obesity 13 with carotid IMT.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…4 A graded and independent association of WHR and BMI with carotid IMT was found in a cross-sectional study in middle-aged women. 12 WHR and BMI were also directly associated with carotid IMT in a crosssectional study among Japanese men aged 20-78 years. 23 Some studies have not shown an independent association of BMI 14 or measures of abdominal obesity 13 with carotid IMT.…”
Section: Discussionmentioning
confidence: 94%
“…A number of previous studies have evaluated the relationship between obesity and CVD, but only a few have focused on the association between abdominal obesity and preclinical atherosclerosis. 4,12 Few, if any, studies have assessed the association between hip circumference and atherosclerosis. Change in carotid IMT, as assessed by ultrasonography, has been validated as a vascular marker of atherosclerosis progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35,36 CIMT is correlated with adult BMI 37,38 and recent studies have suggested that it is also associated with childhood BMI. However, this systematic review only found two studies, which show a positive independent association between childhood BMI Childhood obesity and adult CVD LJ Lloyd et al and adult CIMT.…”
Section: Carotid-intima Thicknessmentioning
confidence: 99%
“…È stata dimostrata una correlazione diretta tra IMT e rischio di infarto del miocardio e ictus in pazienti senza una storia di malattia vascolare [56], e diverse alterazioni metaboliche, come l'obesità [57], l'insulino-resistenza [58], l'iperandrogenismo [59], sono state largamente accettate come fattori di rischio per l'incremento dell'IMT.…”
Section: Struttura E Funzione Endoteliali Nella Pcosunclassified